A Preliminary Study Investigating Class Characteristics in Gurumukhi Handwriting - Vinny Sharma; Anuwanshi Sharma (Indian Journal of Forensic Medicine and Pathology, 2025)
India has been praised for its diversity, particularly in terms of cast, ethos, dialects, religion, and calligraphies. Brahmi characters are ancient India’s primevalscript system, dating back to the first millennium BCE. The Gurumukhi script is the eleventh most widely used script in the world. The Gurumukhi script is written from left to right and from top to bottom. The common beginnings of the scripts, as well as their divergence, are significant and critical. It is undeniably impossible for an auditor to be familiar with eachcalligraphy, specifically in a nation state like India, where languages and scripts vary greatly. The aim of this paperdefines the class and individual features of Gurumukhi scripts, laying the groundwork for calligraphy forensic testing.